Combining Robot-Assisted Gait Training and Non-Invasive Brain Stimulation in Chronic Stroke Patients: A Systematic Review - Bressi, Federica; Cinnera, Alex Martino; Morone, Giovanni; Campagnola, Benedetta; Cricenti, Laura; Santacaterina, Fabio; Miccinilli, Sandra; Zollo, Loredana; Paolucci, Stefano; Di Lazzaro, Vincenzo; Sterzi, Silvia; Bravi, Marco (Frontiers in Neurology, 2022)
Gait impairment is one of the most common disorders of patients with chronic stroke, which hugely affects the ability to carry out the activities of daily living and the quality of life. Recently, traditional rehabilitation techniques have been associated with non-invasive brain stimulation (NIBS) techniques, which enhance brain plasticity, with the aim of promoting recovery in patients with chronic stroke. NIBS effectiveness in improving gait parameters in patients with chronic stroke has been in several studies evaluated. Robotic devices are emerging as promising tools for the treatment of stroke-related disabilities by performing repetitive, intensive, and task-specific treatments and have been proved to be effective for the enhancement of motor recovery in patients with chronic stroke. To date, several studies have examined the combination of NIBS with robotic-assisted gait training, but the effectiveness of this approach is not yet well established. The main purpose of this systematic review is to clarify whether the combination of NIBS and robot-assisted gait training may improve walking function in patients with chronic stroke. Our systematic review was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Studies eligible for review were identified through PubMed/MEDLINE, Embase, Scopus, and PEDro from inception to March 15, 2021, and the outcomes considered were gait assessments. Seven studies were included in the qualitative analysis of this systematic review, with a total population of 186 patients with chronic stroke. All studies specified technical characteristics of robotic devices and NIBS used, with high heterogeneity of protocols. Methodological studies have shown a significantly greater improvement in walking capacity recorded with 6MWT. Finally, research studies have highlighted a positive effect on walking recovery by combination of robot-assisted gait training with non-invasive brain stimulation. Furthermore, future studies should identify the best characteristics of the combined therapeutic protocols. Systematic Review Registration CRD42021244869.